Analysis of Credit Card Usage Against Business Segmentation Using Agglomerative Hierarchical Clustering - prabudi, shabrina; -, arnita; Siregar , Nugrah Anggara; Afdal, Reza Nur; Nasution, Raudha Izmainy (JURNAL TEKNOLOGI DAN ILMU KOMPUTER PRIMA (JUTIKOMP), 2024)
This study analyzes credit card usage patterns and their impact on business segmentation using the Agglomerative Hierarchical Clustering (AHC) method. AHC was chosen because of its ability to group data in detail, especially for datasets with hierarchical relationships. The dataset includes balances, credit limits, monthly payments, and late history. The study aimed to identify high-risk credit card users in payments so that financial institutions can develop more effective risk management strategies. This study successfully identified customer groups with varying payment risks and offered solutions like debt consolidation and flexible payment programs. These findings contribute to the credit card industry in customer segmentation and credit risk management in the credit card industry.